Kombinasi pijat oksitosin, breast care dan biological nurturing untuk meningkatkan produksi ASI - Silvia Pujiyanti; Susilo Rini; Arlyana Hikmanti (Pelantar Press, 2022)
The postpartum period is a period that is very prone to complications for the mother and baby which if not handled properly can cause problems and even death of the mother and baby. The maternal mortality rate in Indonesia in 2020 is 4,627 cases. It is estimated that about 50% of maternal deaths occur during the puerperium, one of which is caused by breast infections due to swelling or breast engorgement, mastitis, and abscesses. Therefore, to prevent this, some complementary care can be given to postpartum mothers such as oxytocin massage, breast care, and biological nurturing. The purpose of this study was to describe the effect of oxytocin massage care, breast care and biological nurturing on postpartum mothers. The research method used is a case study. It was reported a case of a 21-year-old postpartum mother P1 A0 Ah1 who gave birth to her baby 4 hours ago complaining that her breast milk had come out but it was still low. The results of the case study showed that oxytocin massage, breast care and the biological nurturing were more effective in treating breast complications and increasing milk production.